Smart polymers with light emission ability: millennium products for intelligent displays for navigation in the transportation industry. (1st January 2003) - Talaie, A.; Lee, Y.K.; Jang, J.; Choo, D.J.; Park, S.M.; Lee, J.Y.; Park, S.H.; Huh, G.; Taguchi, T.; Maeder, E.
In this paper, we report on the fabrication, characterisation, and application of new polymeric displays in view of the production of new navigation screens in the transportation industry. Conjugated polymer electroluminescence devices (CPELD) have been fabricated using poly (ppheneylene vinylene) (PPV). In this study, we report on the improvement of PPV-based displays by either adding side groups to the polymer structure or by copolymerisation. The effects, of a side group employed during synthesis, on the PL (Photoluminescence), EL (Electroluminescence) profiles and the light intensity of PPV derivatives were investigated. MEH (Methoxy-EthylHexyloxy) and MCHM (MethoxyCycloHexylMethyloxy) were used as side groups. It was found that the PL and EL intensities of the MCHM-PPV were higher than those of MEH-PPV. MCHM-PPV also demonstrated higher light emission at lower potentials and currents. Using copolymers of these two polymers produced even further improvement in PL intensity.